System Architecture and Mobility Management for Mobile Immersive Communications. (22nd February 2007) - Dowlatshahi, Mehran; Safaei, Farzad
Abstract : We propose a system design for delivery of immersive communications to mobile wireless devices based on a distributed proxy model. It is demonstrated that this architecture addresses key technical challenges for the delivery of these services, that is, constraints on link capacity and power consumption in mobile devices. However, additional complexity is introduced with respect to application layer mobility management. The paper proposes three possible methods for updating proxy assignments in response to mobility management and compares the performance of these methods.